Terra Sigillata from Intercisa-Papsziget (Pannonia Inferior) - Kiss, Alexandra (Rei Cretariae Romanae Fautorum Acta, 2022)
From one of the most well-researched auxiliary fort and its adjacent vicus in Hungary, Intercisa, a total of 1137 pieces of terra sigillata fragments came to light during the rescue excavations conducted in 1967. The concerned area, called Papsziget, is a 90 × 30 m large, island-like territory, situated to the southeast from the fort. It comprised the oldest part of the Roman settlement, which is confirmed by finds dated as late as the Flavian period (terra sigillata and amphora fragments, coins, lamps) found at the site. The purpose of this article is to present the spectrum of the sigillata material and to illustrate how this smaller site fits into the history of the Roman settlement.